1994
DOI: 10.1111/j.1744-6570.1994.tb02412.x
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Functions: An Alternative to Traditional Assessment Center Dimensions?

Abstract: The construct validity of traditional assessment center dimensions was compared with that of a set of alternative constructs based on the functional structure of managerial work. Subjects were 75 middle‐level managers in state government who participated in two developmental assessment centers as part of a centralized management development program. One assessment center measured performance in terms of traditional attribute dimensions and the other in terms of functions performed in managerial work. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…For the four data sets that could be inverted, Sackett and Harris found that the ratings were dominated by exercise factors. Several other studies (e.g., Joyce et al, 1994;Silverman et al, 1986;Sackett & Dreher, 1982;Tarnage & Muchinsky, 1982) support these findings. Overall, the evidence strongly suggests that assessment center ratings are measuring situational-specific performance rather than cross-situational managerial abilities.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…For the four data sets that could be inverted, Sackett and Harris found that the ratings were dominated by exercise factors. Several other studies (e.g., Joyce et al, 1994;Silverman et al, 1986;Sackett & Dreher, 1982;Tarnage & Muchinsky, 1982) support these findings. Overall, the evidence strongly suggests that assessment center ratings are measuring situational-specific performance rather than cross-situational managerial abilities.…”
Section: Discussionsupporting
confidence: 61%
“…They concluded that the dimension ratings did not accurately reflect the abilities they were purported to measure. Several other studies support these findings (e.g., Joyce, Thayer & Pond, 1994;Sackett & Dreher, 1982;Schneider & Schmitt, 1992;Silverman, Dalessio, Woods & Johnson, 1986;Turnage & Muchinsky, 1982). According to Bycio et al, the failure of ACs to demonstrate construct validity may result from the cognitive limitations of the assessors to rate accurately a large number of complex dimensions.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Marsh (1990) considered an incomplete MTMM design and stated that incomplete designs are likely to happen in research based on existing personality instruments. Incomplete MTMM designs also arise frequently in assessment center studies (Arthur, Woehr, & Maldegen, 2000;Bobrow & Leonards, 1997;Harris, Becker, & Smith, 1993;Joyce, Thayer, & Pond, 1994;Lance, Foster, Gentry, & Thoresen, 2004;Lievens & van Keer, 2001;Kudisch, Ladd, & Dobbins, 1997). An assessment center evaluates job candidates' skills and abilities using several methods that are available for the purpose.…”
Section: Introductionmentioning
confidence: 96%